Fund Age, BI Rate, Exchange Rate, Dan Jakarta Islamic Index Pada Net Asset Value Di Islamic Equity Mutual Fund Indonesia - Darmawan, Darmawan (Jurnal Manajemen, 2019)
Net Asset Value (NAV) of islamic equity mutual fund is a benchmark to determine the development of islamic equity mutual fund. There are many factors that is influence NAV of Islamic equity mutual fund such as macroeconomic factors as well as internal variables of the mutual fund. The purpose of this study are to find out the effect of fund age, BI rate, exchange rate, and Jakarta Islamic Index (JII) on NAV of Islamic equity of mutual fund. The method analysis used Panel Data Regression Analysis. The results showed that simultaneously fund age, BI rate, exchange rate, and JII have a effect to NAV of islamic equity mutual fund. Partially, fund age, BI rate, and JII have positif effect to NAV of islamic equity mutual fund and exchange rate has insignificant statistical effect to NAV of islamic equity mutual fund.